2010
DOI: 10.1017/s0007114509993898
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal probiotic-supplemented dietary counselling on pregnancy outcome and prenatal and postnatal growth: a double-blind, placebo-controlled study

Abstract: The perinatal nutritional environment impacts upon the health and well-being of mother and child also in the long term. The aim of the present study was to determine the safety and efficacy of perinatal probiotic-supplemented dietary counselling by evaluating pregnancy outcome and fetal and infant growth during the 24 months' follow-up. Altogether, 256 women were randomised at their first trimester of pregnancy into a control and a dietary intervention group. The intervention group received intensive dietary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
272
1
10

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 323 publications
(287 citation statements)
references
References 48 publications
4
272
1
10
Order By: Relevance
“…Some probiotics have been demonstrated to exert beneficial metabolic effects in experimental models 83 and in human intervention studies [84][85][86][87] . There is also growing appreciation that probiotics may have a role in gut-brain function and CNSrelated conditions, (as reviewed by) 88 .…”
Section: Probioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some probiotics have been demonstrated to exert beneficial metabolic effects in experimental models 83 and in human intervention studies [84][85][86][87] . There is also growing appreciation that probiotics may have a role in gut-brain function and CNSrelated conditions, (as reviewed by) 88 .…”
Section: Probioticsmentioning
confidence: 99%
“…In overweight adults, treatment with galactooligosaccharides induced "favorable" changes in gut microbial composition, increased secretory IgA (sIgA), reduced inflammation and measures of the metabolic syndrome 92 . Notably, the combination of a healthy dietary intervention (increased fiber/reduced fat) and probiotics in pregnancy decreased the risk of gestational diabetes compared with the healthy dietary intervention alone or no intervention 87 . Either alone, or in combination, dietary approaches may be a useful tool for gut microbiota modulation in both the treatment and prevention of NCDs.…”
Section: West 16mentioning
confidence: 99%
“…Interestingly, nutrition counseling and probiotic intervention have been shown to have a different effect on mothers suffering gestational diabetes (GD), whereby probiotics reduce the risk of the disorder while dietary counseling reduces the risk of fetal macrosomia and overgrowth as GD consequence (73). A recent meta-analysis showed a significant reduction in the prevalence and incidence of atopic eczema in children aged 2-7 y whose mothers received probiotics during pregnancy (74).…”
Section: Diet and Microbes: Tools To Modify Early Microbial Expositionmentioning
confidence: 99%
“…Other studies also confirmed that the number of bifidobacteria is lower in obese than in lean individuals [41]. The composition of the gut microbiota in maternal colostrum, or in measured babies, suggest bifidobacteria count might be considered as an index of maintenance of healthy body weight [42••], [43]. Recent reports suggest that the level of bifidobacteria is dependent on the dietary intake because weight loss after bariatric surgery is associated with reduced Bifidobacterium [44••],whereas decreased Bifidobacterium bifidum and Bifidobacterium breve counts and increased Bifidobacterium catenulatum are observed upon weight loss upon dietary intervention in adolescents [45].…”
Section: Changes In Microbiota Composition Related To Diabetes and Inmentioning
confidence: 93%